(3GdeHOC hGdeYGO (B( (3YfO GdeTGFjf(B)s - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEfi CQjO Cf Chd ai gPg GdebGdI Ydi MbjbI eG YfO GdeTGFjf s
(3BNQgG (B:s
(3hEf cGfJ ef GdbhI HMjK GdChdi Cf JPcQ hdcf eDKQ GdGaUGM hGdGNJUGQ Ef eGd Edi GdGXgQ agh eYPhQ hfSCd Gddg GdJhajb Je GdcJGH hddg GdMeO hGdefg ceG gh eSJMbg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs